A Relationship between Information Technology Implementation and Acquisition of Competitive Advantages in Banking in Croatia - Denis Hrestak (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Strong development of information technology corresponds to a growing corporate investment into this segment, especially in the field of financial services and telecommunications. This work aims to investigate whether these investments make sense, and do they contribute to the company success. This paper presents the results of qualitative research based on a field research and quantitative econometric analysis of the banking sector's statistical data in the Republic of Croatia in order to determine relationship between information technology and electronic business implementation, and achievement of competitive advantage in the banking sector, operational costs reduction and business efficiency increase. In the theoretical part, this paper describes the role of information technology in business, development and strategic role of e-business, e-business models, and especially important, the business aspects of electronic commerce in the banking sector. Conclusion shows that there is a strong positive linear relationship between the application of ICT and achievement of a competitive advantage in the banking sector. Also, the cost per executed transaction is reduced, and there is a strong positive correlation between investments in e-business and business performance.
Keywords: O330; 330; ICT; technology; banking; Croatia; investment; research